Adjusted versus unadjusted earnings: An empirical analysis of pro forma adjustments in large German public companies - Marcel Wiek; Korbinian Eichner (Journal of Corporate Accounting & Finance, 2023)
This article analyzes non-GAAP, pro forma earnings metrics of large German publicly traded companies to better understand their usage and relevance in practice. We base our analysis on a hand collected data set compiled from annual reports. Almost all companies in our data set use pro forma earnings. Typically, legal, restructuring, acquisition and accounting related costs get adjusted. EBIT, EBITDA, EPS and Net income are the most frequently adjusted earnings metrics. In almost all observed cases, pro forma earnings are higher than their underlying GAAP earnings. Our study addresses the challenge of investors to understand a company's “true” operating performance. Only when one understands the historically observable financial performance, one can make better predictions of its recurring, future financial performance. The article adds to the existing literature by analyzing in which part of the annual report pro forma earnings are typically disclosed, how transparent they are presented and reconciled, and what impact adjustments have compared to the unadjusted GAAP earnings.
Keywords: 650; asymmetric information; corporate finance; corporate valuation; financial reporting; market approach